Suficiência amostral para uma floresta de miombo no distrito de mocuba, província da Zambézia, em Moçambique - Hofiço, Noé dos Santos Ananias (2014)
The aim of this study was to determine sample sufficiency for phytosociological studies and inventories of wood in a forest area of Miombo woodland in Mocuba district, Zambezia province, Mozambique. The study area was represented by a systematic sampling grid that contains 128 sampling units ranging from 0.1 to 1.0 ha, inserted into 16 tracks, with eight units in each, arranged randomly and independent of each other. All individuals with Cbh ≥ 31.5 cm were measured and identified. Obtained the parameters of the floristic composition, horizontal structure, diversity using Shannon-Wienner, by the evenness index of Pielou and sampling sufficiency was evaluated based on analysis of curve species/area. The behavior of the diameter distribution curves were fitted to the treatment function Meyer and statistically compared by Chi-square (χ2), adopting α = 5% and was found by analysis of covariance showed that the same level differences and gradients among themselves. The selection of the size of the sampling units was based on the stability of the coefficient of variation in the relative sampling error; the fewer sized sampling units and the practicality of applying the methodology in the field. In the area 36535 individuals distributed, on average occurred in 516.6 ind.ha-1, with a mean basal area of 26.21 m2.ha-1. The richest botanical family was Fabaceae. The most important species was the Brachystegia spiciformis forest showed a high species diversity and evenness. Observed stability curve species/area from 4.0 ha area covered with the occurrence of 86 species. The diameter distribution curves were not adherent by χ2 test for size 0.1 ha and 0.25 ha and covariance analysis showed no difference in slope between level and sizes can use a single regression. The sampling units of 0.25 ha (50m x 20m) had lower sampling errors of 10% in the estimation of basal area for groups of commercial species. The estimated basal area at the species level was found to be not accurate due to the low frequency of individuals per hectare